Sistem Informasi Berbasis Web Tentang Pelaporan Perkembangan Kelompok Usaha Bersama (Kube) - Gatot Safitri; Ifan Junaedi; Akmal Budi Yulianto (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
The development of technology that is built to fix a problem in a system is needed by the institution. The Directorate of Poor Handling Region III, Ministry of Social Affairs of the Republic of Indonesia requires an information system for reporting recipients of assistance quickly and periodically. In this case, the author conducted a study that aims to develop a reporting information system, so that the development of the Joint Business Group (KUBE) beneficiaries can be known quickly and as information material for decision makers related to program implementation. By analyzing the current system, this research resulted in the development of a web-based information system on reporting the development of the Joint Business Group (KUBE) at the Directorate of Poor Handling Region III, Ministry of Social Affairs, RI. The development of this system refers to the System Development Life Cycle (SDLC) with the Waterfall model. Reports on the development of the Joint Business Group (KUBE) are carried out by social assistants and the report will make it easier for the Directorate for the Handling of the Poor Region III to obtain information on the progress of KUBE assistance.